Technical report - Corps of Engineers, U.S. Army, Cold Regions Research and Engineering Laboratory. - Cold Regions Research and Engineering Laboratory (U.S.)
Issued out of chronological order. Mode of access: Internet. Merged with: Research report - Corps of Engineers, U.S. Army, Cold Regions Research and Engineering Laboratory, ISSN 0501-5812, to form: CRREL report, ISSN 0501-5782.